Tumor testing to identify lynch syndrome in two Australian colorectal cancer cohorts. Issue 2 (February 2017) - Buchanan, Daniel D; Clendenning, Mark; Rosty, Christophe; Eriksen, Stine V; Walsh, Michael D; Walters, Rhiannon J; Thibodeau, Stephen N; Stewart, Jenna; Preston, Susan; Win, Aung Ko; Flander, Louisa; Ait Ouakrim, Driss; et al.
Abstract: Background and Aim: Tumor testing of colorectal cancers (CRC) for mismatch repair (MMR) deficiency is an effective approach to identify carriers of germline MMR gene mutation (Lynch syndrome). The aim of this study was to identify MMR gene mutation carriers in two cohorts of population‐based CRC utilizing a combination of tumor and germline testing approaches. Methods: Colorectal cancers from 813 patients diagnosed with CRC < 60 years of age from the Australasian Colorectal Cancer Family Registry (ACCFR) and from 826 patients from the Melbourne Collaborative Cohort Study (MCCS) were tested for MMR protein expression using immunohistochemistry, microsatellite instability (MSI), BRAF V600E somatic mutation, and for MLH1 methylation. MMR gene mutation testing (Sanger sequencing and Multiplex Ligation Dependent Probe Amplification) was performed on germline DNA of patients with MMR‐deficient tumors and a subset of MMR‐proficient CRCs. Results: Of the 813 ACCFR probands, 90 probands demonstrated tumor MMR deficiency (11.1%), and 42 had a MMR gene germline mutation (5.2%). For the MCCS, MMR deficiency was identified in the tumors of 103 probands (12.5%) and seven had a germline mutation (0.8%). All the mutation carriers were diagnosed prior to 70 years of age. Probands with a MMR‐deficient CRC without MLH1 methylation and a gene mutation were considered Lynch‐like and comprised 41.1% and 25.2% of the MMR‐deficient CRCs for the ACCFR and MCCS, respectively. Conclusions: Identification of MMR gene mutation carriers in Australian CRC‐affected patients is optimized by immunohistochemistry screening of CRC diagnosed before 70 years of age. A significant proportion of MMR‐deficient CRCs will have unknown etiology (Lynch‐like) proving problematic for clinical management.